2004
DOI: 10.1603/0013-8746(2004)097[0194:dbrtwc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Differential Behavioral Responses to Water-Borne Cues to Predation in Two Container-Dwelling Mosquitoes

Abstract: Larvae of the mosquito Toxorhynchites rutilus (Coquillett) prey upon other container-dwelling insects, including larvae of Aedes albopictus (Skuse), which is native to Asia but was introduced into the United States, and on the native tree hole mosquito Ochlerotatus triseriatus (Say). Previous work has established that O. triseriatus adopts low-risk behaviors in the presence of predation risk from T. rutilus. It is unknown whether introduced A. albopictus show a similar response to this predator. Behavior of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 17 publications
(28 reference statements)
6
111
2
Order By: Relevance
“…Despite this, Lounibos et al (2001) reported that O. triseriatus have not been replaced by A. albopictus in the Weld, especially in tree holes in wooded habitat. Behavioral responses of A. albopictus to water-borne cues to risk of predation are either absent (Kesavaraju and Juliano 2004) or of much smaller magnitude than those of native O. triseriatus (Kesavaraju et al 2007a). This likely contributes to greater vulnerability of A. albopictus to predation by C. appendiculata (and to other predators like Toxorhynchites rutilus (order, Diptera; family, Culicidae) compared to O. triseriatus (Lounibos et al 2001;Griswold and Lounibos 2005a;Griswold and Lounibos 2005b).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite this, Lounibos et al (2001) reported that O. triseriatus have not been replaced by A. albopictus in the Weld, especially in tree holes in wooded habitat. Behavioral responses of A. albopictus to water-borne cues to risk of predation are either absent (Kesavaraju and Juliano 2004) or of much smaller magnitude than those of native O. triseriatus (Kesavaraju et al 2007a). This likely contributes to greater vulnerability of A. albopictus to predation by C. appendiculata (and to other predators like Toxorhynchites rutilus (order, Diptera; family, Culicidae) compared to O. triseriatus (Lounibos et al 2001;Griswold and Lounibos 2005a;Griswold and Lounibos 2005b).…”
Section: Discussionmentioning
confidence: 97%
“…Dead, eaten, and pupated individuals were replaced daily. The test subjects, F 1 generation A. albopictus from the different sites, were hatched and held in 5 ml of water in 4 dram vials and fed with 1 ml of liver powder suspension prepared by stirring 0.3 g of liver powder in 1,000-ml beaker with 1,000 ml water on a stir plate and transferred using an Eppendorf pipette (Juliano and Gravel 2002;Kesavaraju and Juliano 2004). A single feeding was sufficient for A. albopictus to develop to second instar.…”
Section: Behavioral Difference Among Sitesmentioning
confidence: 99%
“…Generally, time spent foraging correlates positively with the likelihood of being detected by visual predators or encountering ambush predators, and so individuals typically decrease foraging under predation risk (Lima and Dill 1990;Benard 2004;Stoks et al 2005). Also C. pipiens larvae were found to move less when exposed to kairomones from a heteropteran predator, the backswimmer Notonecta undulata (Sih 1986), and reduced foraging under the influence of predator kairomones was also reported from other culicid larvae (Kesavaraju and Juliano 2004;Ohba et al 2012). Adaptive growth reduction in response to fish kairomones allows mosquito larvae (Culex pipiens… Moreover, we detected another effect-reduced body size-that was strongest in the treatment with stickleback kairomones, considerably weaker when kairomones of insectivorous, but not co-evolved, Gambusia were present, while no effect at all was seen in the Ancistrus treatment.…”
Section: Discussionmentioning
confidence: 89%
“…This fact was consistent with the finding that Ae. albopictus was more susceptible to predation by Toxorhynchites rutilus (Coquillett) compared with some native species (Kesavaraju and Juliano 2004), and that tree holes harbored more of this predator than other systems (Yee et al 2012b, Freed and. It also provided evidence for the influence of detritus type and amount in affecting populations of Ae.…”
Section: Nutrient Environmentsmentioning
confidence: 99%